An entomological review of invasive mosquitoes in Europe. Issue 6 (25th March 2015) - Medlock, J.M.; Hansford, K.M.; Versteirt, V.; Cull, B.; Kampen, H.; Fontenille, D.; Hendrickx, G.; Zeller, H.; Van Bortel, W.; Schaffner, F.
Abstract: Among the invasive mosquitoes registered all over the world, Aedes species are particularly frequent and important. As several of them are potential vectors of disease, they present significant health concerns for 21st century Europe. Five species have established in mainland Europe, with two ( Aedes albopictus and Aedes japonicus ) becoming widespread and two ( Ae. albopictus and Aedes aegypti ) implicated in disease transmission to humans in Europe. The routes of importation and spread are often enigmatic, the ability to adapt to local environments and climates are rapid, and the biting nuisance and vector potential are both an ecomonic and public health concern. Europeans are used to cases of dengue and chikungunya in travellers returning from the tropics, but the threat to health and tourism in mainland Europe is substantive. Coupled to that are the emerging issues in the European overseas territorities and this paper is the first to consider the impacts in the remoter outposts of Europe. If entomologists and public health authorities are to address the spread of these mosquitoes and mitigate their health risks they must first be prepared to share information to better understand their biology and ecology, and share data on their distribution and control successes. This paper focusses in greater detail on the entomological and ecological aspects of these mosquitoes to assist with the risk assessment process, bringing together a large amount of information gathered through the ECDC VBORNET project.